The effects of exercise training on physical performance and self-efficacy in hemodialysis patients: A randomized controlled clinical trial - Marzieh Hatef; Nouraddin Mousavinasab; Ravanbakhsh Esmaeili; Mahsa Kamali; Zahra Madani; Fatemeh Spahbodi; Vida Shafipour (Wolters Kluwer Medknow Publications, 2020)
Background: Hemodialysis patients are faced with challenges in carrying out their daily activities. Self-efficacy is a social cognitive concept that can affect behavioral control in these patients. Hence, the purpose of the present study was to investigate the effects of exercise training on physical performance and self-efficacy in hemodialysis patients. Materials and Methods: This randomized controlled clinical trial was conducted on 60 hemodialysis patients who visited hospitals affiliated to Mazandaran University of Medical Sciences in Sari, Iran. The participants were randomly divided into two groups. The patients in the intervention/exercise group received the 8-week exercise program. Patients in the control group received routine care. The Six-Minute Walk Test (6MWT) was used to assess the patients' functional ability and the Exercise Self-Efficacy Scale (ESES) and Chronic Disease Self-Efficacy Scale (CDSES) were used to assess their self-efficacy before and 2 and 8 weeks after the intervention. For statistical analysis, independent t-test and paired t-test were used. Results: The comparison of self-efficacy between the exercise group and control group after 8 weeks of intervention showed a significant difference between the groups in terms of the CDSES (F1,43= 22.92, p < 0.001) and ESES (F1,38= 10.84, p < 0.001) results. Moreover, the comparison of mean distance walked based on the 6MWT showed significant changes in this variable (F1= 2.05, p = 0.015). Conclusions: The designed exercise program can improve self-efficacy and physical performance in hemodialysis patients. This intervention is recommended for hemodialysis patients due to its effectiveness, simplicity, and uncomplicated characteristics